2023
DOI: 10.2147/ijwh.s406596
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Vaginal Microbiota and Immunity: Two Main Accomplices of Cervical Cancer in Chinese Women

Abstract: Objective To explore the correlation of female vaginal microbiota and immune factors with cervical cancer. Methods The distribution pattern difference of vaginal microbiota of four groups of women (cervical cancer, HPV-positive CIN, HPV-positive non-CIN, and HPV-negative groups) were compared by microbial 16S rDNA sequencing. The protein chip was used to detect the composition and changes of the immune factors in the four groups. Results Alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Female genital cancer can develop due to various factors, such as viruses, bacteria, and hormonal and genetic imbalances. In recent years, research has shown that the microbiome also plays a significant role in cancer development; additionally, HPV infection increases the risk of developing squamous cell carcinoma in the skin and mucous membranes [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Female genital cancer can develop due to various factors, such as viruses, bacteria, and hormonal and genetic imbalances. In recent years, research has shown that the microbiome also plays a significant role in cancer development; additionally, HPV infection increases the risk of developing squamous cell carcinoma in the skin and mucous membranes [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%